POSSIBLE WORLDS FOR FICTION. A RECONSTRUCTIVE APPROACH, WITH A PRACTICAL OUTLOOK INTO IAN MCEWAN’S ATONEMENT, ON CHESIL BEACH AND THE CHILD IN TIME - Adriana Diana URIAN (Studia Universitatis Babeş-Bolyai. Philologia)
Possible Worlds for Fiction. A Reconstructive Approach, With a Practical Outlook into Ian McEwan’s Atonement, On Chesil Beach and The Child in Time. The present paper aims at presenting how the possible world framework can function for fictional worlds. It starts from presenting different perspectives on how fictional universes can be understood. It then grounds its reconstructive approach in modal logic theories, such as the ones postulated by Kripke and Lewis, attempting to find a possible world system which can be adapted and become custom-fit for fiction. The theoretical approach favorizes re-creations of the modal system for fiction, as presented by Marie-Laure Ryan or Ruth Ronen. The study of this particular topic is eclectic, putting together various perspectives on literature, fiction and modality. The theoretical input is accompanied by practical reverberations from the three novels presented in the title, which function as its scientific playground.